Particulate Backscattering Ratio as an Indicator of Changing Particle Composition in Coastal Waters: Observations From Great Barrier Reef Waters. Issue 8 (4th August 2019) - Soja‐Woźniak, Monika; Baird, Mark; Schroeder, Thomas; Qin, Yi; Clementson, Lesley; Baker, Brett; Boadle, David; Brando, Vittorio; Steven, Andy D. L.
Abstract: Particle scattering is an important process that determines both the light penetration through the water column and water‐leaving light. Backscattering, in combination with absorption, determines the remote‐sensing reflectance that is used in ocean color algorithms. Additionally, the wavelength dependence of the backscattering ratio can be related to the particle composition in seawater. Here, we examine the magnitude and the spectral behavior of the backscattering ratio against other bio‐optical properties based on a comprehensive set of continuous measurements collected in coastal waters of the Great Barrier Reef over 3 years. The site is located offshore of a major river, and close to the cross‐shelf transition of bottom sediments from terrigenous muds to marine carbonates. The backscattering ratio measured at 650 nm clearly clustered the data into two types. Type 1, which we identified as terrigenous mud with a low organic fraction, is characterized by backscattering ratio below 0.011 with a mean value of 0.005. Type 2, which we identified as marine carbonate with a higher organic fraction, has backscattering ratio above 0.011 with a mean value of 0.02. Within 3 years, study site was exposed to type 1‐dominated particles 13% of the time, and type 2 87%. The observed changes in the backscattering ratio at this one coastal site are as large as the variability seen throughout the global ocean. This work provides a better understanding of processes determining the optical characteristics and insights into optical parameterizations that can be used in process‐based optical modeling of the Great Barrier Reef. Key Points: The backscattering ratio at 650 nm measured at Lucinda Jetty Coastal Observatory clearly clustered the data into two types During the study, the estimated exposure of the observatory to terrigenous mud and marine carbonate was 13% and 87%, respectively The observed changes in the backscattering ratio at the study site are as large as the variability seen throughout the global ocean